An accelerating channel of intermediate part of high-current proton linac based on combined focusing by rf field - Tishkin, S.S.; Shulika, M.G.; Shulika, O.M. (Вопросы атомной науки и техники, 2020)
Particle dynamics in an accelerating-and-focusing channel of intermediate part of a proton linac based on combined rf-focusing under following conditions: energy range 3…100 MeV, current 100 mA, and acceleration rate 5 MeV/m, is studied. To implement combined rf-focusing, it is proposed to use accelerating structures of two different types: an Interdigital IH-type structure allows acceleration in the range of 3 to 20 MeV, while a Crossbar CHtype structure accelerates particles from 20 up to 100 MeV. Also, methods to adjust rf-field amplitude in quadrupole gaps for both (IH and CH) structures are discussed. Досліджено динаміку частинок у каналі, що прискорює та фокусує, середньої частини протонного прискорювача з комбінованим високочастотним фокусуванням у діапазоні енергій 3…100 МеВ для струму 100 мА з темпом прискорення 5 МеВ/м. Запропоновано схему реалізації даного варіанту фокусування на основі двох типів структур, що прискорюють. У діапазоні енергій 3…20 МеВ запропоновано використовувати IH-структуру, а для діапазону енергій 20…100 МеВ – CH-структуру. Розглянуто методи налаштування амплітуди високочастотних полів у квадрупольних зазорах для IH- та CH-структур. Исследована динамика частиц в ускоряюще-фокусирующем канале промежуточной части протонного ускорителя с комбинированной высокочастотной фокусировкой в диапазоне энергий 3…100 МэВ для 100 мА тока с темпом ускорения 5 МэВ/м. Предложена схема реализации данного варианта фокусировки на базе двух типов ускоряющих структур. В диапазоне энергий 3…20 МэВ предложено использовать IH-структуру, а в диапазоне 20…100 МэВ – CH-структуру. Рассмотрены методы настройки амплитуды высокочастотных полей в квадрупольных зазорах для IH- и CH-структур.